PENGUATAN PROFESIONALISME GURU PAI DI ERA DISRUPSI - Lalu Muhammad Samiuddin; Aris Setyawan; Kamarul Zaman; Ine Ratu Fadilah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2025)
The era of disruption, characterized by the development of digital technology, rapid social change, and shifts in values ​​and culture, demands transformation in the world of education, including in the professionalism of Islamic Religious Education (PAI) teachers. PAI teachers are not only required to master Islamic material normatively, but also to be able to adapt to changing times, master learning technology, and possess strong pedagogical, professional, social, and personality competencies. This article aims to examine in depth the concept of strengthening the professionalism of PAI teachers in the era of disruption, the factors that influence it, and development strategies. This study uses a qualitative approach with a library research method on various literature sources in the form of books, scientific journals, and educational policy documents. The results show that strengthening the professionalism of PAI teachers must be carried out holistically through improving digital competencies, strengthening the values ​​of religious moderation, developing innovative learning, and providing policy and institutional support. Thus, PAI teachers are expected to be able to carry out their role optimally in shaping students who are religious, moderate, and adaptive to the challenges of the times.